(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background Basic Life Support training significantly enhances the skills, confidence, and retention of nursing students in emergency response, especially when simulation-based and interactive learning methods are used. Research shows that this type of training increases CPR proficiency, and ensures long-term competency. Objective: To evaluate the impact of BLS training on the knowledge of bachelor of science in nursing students’ and how BLS training effects the practical application of nursing students in lifesaving activities. Method: A quasi-experimental study design with pretest, post immediate test and post test was conducted at Rashid Latif nursing college. Non-probability purposive sampling technique was used for the selection of 126 participants. The training included a power point presentation, hands on practice and video demonstration. Data were collected from the participants. Data analysis was performed via SPSS version 23 with Fredman’s ANOVA used for statistical analysis. Result: The findings show noteworthy improvement in BLS knowledge during assessment periods. During the pre-test, respondents were poor mean score (mean=48.9%), (mean=68.3%) average, and none good. Immediate post-test results indicated remarkable improvement, with good score (mean=96.5%) and poor (mean=28.55%). Knowledge retention continued to be excellent at one-month follow-up showing good scores (mean=91.6%) and poor scorers reducing to (mean=23.8%) with average scorers rising to (mean=81.0%). Results suggest that BLS training succeeds in enhancing as well as retaining knowledge among nursing students. Conclusion: After the training there was a significant effect on the knowledge of BS nursing students. However, there was a noticeable decrease in knowledge retention with time.